2023
DOI: 10.1007/s12291-022-01108-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Circulatory Cytokines and Chemokines Levels in Mild to Severe COVID-19 Patients

Abstract: Immune dysregulation is a key feature of the coronavirus disease-2019 (COVID-19). However, disparities in responses across ethnic groups are underappreciated. This study aimed to determine the relationship between chemokines and cytokines and the severity of COVID-19. Multiplex magnetic bead-based Luminex-100 was used to assess chemokine and cytokine levels in COVID-19 patients at admission (day-1) and after 4 days. The mean age of the patients recruited was 54.3 years, with 19 (63.3%) males. COVID-19 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Activated T cells, including the CD4 + T, CD8 + T, and Th cells, were found enriched in COVID-19 participants ( Rupp et al, 2021 ; Qin et al, 2023 ). Moreover, cytokine levels were shown to be higher in COVID-19 participants ( Hasanvand, 2022 ; Queiroz et al, 2022 ; Tiwari et al, 2023 ). As aGVHD is mediated by the activation of alloreactive T cells with high level of cytokine and chemokine ( Lange et al, 1995 ; Zeiser and Blazar, 2017 ; Khandelwal et al, 2020 ), we presume that increased aGVHD in the CPD group might be attributed to the active T cells and cytokines in graft derived from COVID-19-positive donors.…”
Section: Discussionmentioning
confidence: 96%
“…Activated T cells, including the CD4 + T, CD8 + T, and Th cells, were found enriched in COVID-19 participants ( Rupp et al, 2021 ; Qin et al, 2023 ). Moreover, cytokine levels were shown to be higher in COVID-19 participants ( Hasanvand, 2022 ; Queiroz et al, 2022 ; Tiwari et al, 2023 ). As aGVHD is mediated by the activation of alloreactive T cells with high level of cytokine and chemokine ( Lange et al, 1995 ; Zeiser and Blazar, 2017 ; Khandelwal et al, 2020 ), we presume that increased aGVHD in the CPD group might be attributed to the active T cells and cytokines in graft derived from COVID-19-positive donors.…”
Section: Discussionmentioning
confidence: 96%
“…By investigating the correlation between admission symptoms and cytokine levels, the study revealed that symptomatic individuals exhibited elevated TGFalpha, GRO-alpha, IL-6, and IL-10, con rming these as pivotal cytokines in immune responses and symptom development during viral infections (21). The elevated levels of TGF-alpha, GRO-alpha, IL-6, and IL-10 in symptomatic individuals relative to asymptomatic ones suggest their potential as biomarkers for early COVID-19 symptom manifestation or immune activation, due to their critical roles in cell growth, chemotaxis, in ammation modulation, and immune regulation (22)(23)(24), thus suggesting a potential role in viral infection pathogenesis and symptom presentation. Random Forest analysis predicted and delineated pivotal cytokines over different time points, elucidating their roles and potential as therapeutic targets and underscoring their dynamic contributions to immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a larger study, we look to validate the prodrug activity of these compounds and uncover whether this approach has any efficacy against the oxidative stress side effects related to the use of glucocorticoids. [60][61][62][63][64] Aside from their prospective therapeutic actions, the confirmed binding of the nitroxide hybrids to GR suggests they may also offer some use as spin-labelled steroid probes. 65,66 In summary, to produce new hybrid systems capable of probing biological radical chemistry, we have synthesised a number of nitroxide-steroidal hybrids and non-radical control molecules using carbodiimide coupling.…”
Section: Paper Synthesismentioning
confidence: 99%